2021
DOI: 10.1101/2021.03.10.21253331
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Disulfiram associated with lower risk of Covid-19: a retrospective cohort study

Abstract: In the global COVID-19 pandemic, there is a substantial need for effective, low-cost therapeutics. We investigated the potential effects of disulfiram on the incidence and outcomes of COVID-19 in an observational study in a large database of US Veterans Administration clinical records, the VA Corporate Data Warehouse (CDW). The study is motivated by the unique properties of disulfiram, which has been used as an anti-alcoholism drug since 1948, is non-toxic, easy to manufacture and inexpensive. Disulfiram reduc… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Dimethyl fumarate (DMF), an FDA-approved therapeutic for multiple sclerosis, as well as fumarate, the endogenous Krebs cycle intermediate related to DMF, was recently shown to inhibit GSDMD 168 . Interestingly, a case series of several patients with multiple sclerosis being treated with DMF showed that their SARS-CoV-2 infection was self-limiting without their receiving any specific treatment 169 , and an observational study using a large health-care database revealed a significantly reduced risk of SARS-CoV-2 infection and no death in the group using DSF for alcoholism compared with a control group, but this study has not been fully peer reviewed 170 . DSF is currently being studied in two controlled phase II clinical trials that are testing efficacy in mild to moderate disease (NCT04485130) as well as in patients who are hospitalized (NCT04594343) (Table 1 ).…”
Section: Clinical Interventionsmentioning
confidence: 96%
“…Dimethyl fumarate (DMF), an FDA-approved therapeutic for multiple sclerosis, as well as fumarate, the endogenous Krebs cycle intermediate related to DMF, was recently shown to inhibit GSDMD 168 . Interestingly, a case series of several patients with multiple sclerosis being treated with DMF showed that their SARS-CoV-2 infection was self-limiting without their receiving any specific treatment 169 , and an observational study using a large health-care database revealed a significantly reduced risk of SARS-CoV-2 infection and no death in the group using DSF for alcoholism compared with a control group, but this study has not been fully peer reviewed 170 . DSF is currently being studied in two controlled phase II clinical trials that are testing efficacy in mild to moderate disease (NCT04485130) as well as in patients who are hospitalized (NCT04594343) (Table 1 ).…”
Section: Clinical Interventionsmentioning
confidence: 96%
“…As they have been identified as GSDMD-inhibitors, their clinical trials are ongoing for the treatment of COVID-19 disease (Vora et al, 2021). In fact, COVID-19 patients under DMF treatment against sclerosis or under DSF against alcohol use disorder showed a self-limiting symptoms (Fillmore et al, 2021;Mantero et al, 2021). Therefore, it is being clinically tested against COVID-19 (trial number NCT04594343) with a treatment dose of 120 mg every 12 hours for 2 days or 240 mg every 12 hours for 8 days.…”
Section: Gsdmd Inhibitorsmentioning
confidence: 99%
“…This network pharmacology workflow has enabled us to identify some relevant drugs as candidates for drug repurposing for the treatment of COVID-19 progression based on the viral and human protein interactions observed in our networks. Some of the drugs identified in the present study have in fact been proposed as candidates for the treatment of COVID-19 by different authors, for example, 1) disulfiram, where its uses are associated with a lower risk of COVID-19 (Fillmore et al, 2021); 2) auranofin, which inhibits SARS-CoV-2 replication and attenuates inflammation in human cells (Marzo and Messori, 2020;Rothan et al, 2020); 3) suloctidil, which was recommended for the treatment of COVID-19-induced exacerbation of asthma (Guo et al, 2021); and 4) gefitinib, which was reported to inhibit spike-driven fusion (Braga et al, 2021).…”
Section: Discussionmentioning
confidence: 85%